2017
DOI: 10.1371/journal.pone.0176816
|View full text |Cite
|
Sign up to set email alerts
|

No relevant association of kinematic gait parameters with Health-related Quality of Life in Parkinson’s disease

Abstract: BackgroundHealth-related Quality of Life (HrQoL) is probably the most important outcome parameter for the evaluation and management of chronic diseases. As this parameter is subjective and prone to bias, there is an urgent need to identify objective surrogate markers. Gait velocity has been shown to be associated with HrQoL in numerous chronic diseases, such as Parkinson’s disease (PD). With the development and wide availability of simple-to-use wearable sensors and sophisticated gait algorithms, kinematic gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…While this argument is comprehensible, the EQ-5D indubitably has been commonly used for the assessment of QoL in many different patient populations, including PD patients [34][35][36] and it is reasonable that this instrument will also be used frequently in future studies, not least because of its simplicity and brevity [37]. Due to this, a direct comparison of the EQ-5D…”
Section: Discussionmentioning
confidence: 99%
“…While this argument is comprehensible, the EQ-5D indubitably has been commonly used for the assessment of QoL in many different patient populations, including PD patients [34][35][36] and it is reasonable that this instrument will also be used frequently in future studies, not least because of its simplicity and brevity [37]. Due to this, a direct comparison of the EQ-5D…”
Section: Discussionmentioning
confidence: 99%
“…The reason relates to a mismatch between a patient’s functional needs, preferences and environmental constrains, and health professionals’ perspectives. In 2017, Bettecken et al [ 48 ] reported a relationship between PD patients’ gait velocity using an assistive mobile device and their HrQoL. Surprisingly, the study did not show a relevant contribution of gait velocity to HrQoL.…”
Section: Improving Functional Mobility In Pdmentioning
confidence: 98%
“…More studies are needed to understand the relationship between the use of assistive mobility devices, PD patients’ functional mobility and HrQoL. Perceived control may be the key aspect in explaining the intriguing conclusion that Bettecken and colleagues found in their study [ 48 ]. As mentioned above, perceived control is a powerful predictor of functioning and it seems that some patients place more value on the capability of performing ADL rather than the time it takes to perform specific tasks [ 26, 49 ].…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 99%
“…As motor impairments progress, the risk of falls increases and patients become more dependent (for example, being in need of using walking aids). Both factors are associated with reduced quality of life (4,7). To detect motor impairment in PD, wearable devices have been increasingly used in recent years as a flexible and cost-effective option in clinical settings (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Both factors are associated with reduced quality of life (4,7). To detect motor impairment in PD, wearable devices have been increasingly used in recent years as a flexible and cost-effective option in clinical settings (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%